Qualidade de vida de mães de crianças e adolescentes com doenças neurológicas crônicas incapacitantes - Rodrigues, Ana Karine Mendes (2011)
Disabling chronic neurological diseases such as cerebral palsy (CP), myelomeningocele (MM), Down syndrome (DS) and autistic disorder (AD) are still prevalent in childhood and limit various aspects of child development. Although there is a major negative impact on the health related quality of life (HRQL) of the mothers of affected children, so far no comparative studies have been performed to tell whether these diseases compromise the mothers HRQL in a different way, and whether there is an association of demographic characteristics with HRQL. The intention of this study is to evaluate the HRQL of mothers of children and adolescents with CP, MM, DS and AD, comparing them to each other and to the group of mothers of healthy children and adolescents and to look at the demographic characteristics of mothers of children and adolescents with disabling neurological diseases and their association with HRQL. One hundred and thirty-seven mothers with children and adolescents with CP, MM, DS and AD and 208 mothers with healthy children and adolescents participated. All the mothers answered the Medical Outcomes Study 36- Item Short Form Health Survey (SF-36) and protocol with demographic information. The Alfa Cronbach coefficient was calculated to determine the reliability of the instrument. The demographic variables and the SF-36 scores of mothers of children and adolescents with disabling neurological diseases were compared to the healthy group together or separately according to their child`s diagnosis (Mann-Whitney, Kruskal-Wallis or Chi-Square tests). The SF-36 scores achieved by the mothers of the group with disabling neurological diseases were compared to the demographic variables (Kruskal-Wallis or Mann-Whitney tests) and correlated to the age of mothers, number of children and family income (Spearman correlation coefficient). Mothers in the group with disabling neurological diseases had lower scores than healthy group (p<0.05) in most domains, when compared together or separately according to their child`s diagnosis. There was no significant difference in the HRQL among the mothers of children and adolescents with CP, MM, DS and AD. Mothers of children and adolescents with disabling neurological diseases presented a lower frequency of continued employment, a higher frequency of stable marital unions and higher family income compared to the healthy group. Older mothers or widows had lower scores in the physical dimension of SF-36 (p<0.05). Concluding, mothers of children and adolescents with CP, MM, DS and AD presented multidimensional impairment in HRQL, compared to the mothers of healthy children and adolescents, but this negative impact was not different from the groups of mothers of children and adolescents with disabling neurological diseases. The negative impact on HRQL was greater in the physical dimension among older mothers or widows.